2022
DOI: 10.1038/s41598-022-10354-1
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate trees quality under drought conditions using potassium silicate, nanosilver, and selenium spray with valorization of peels as fungicide extracts

Abstract: The current study was performed on 8 years old "Succary" pomegranate cultivar (Punica granatum L.) during the 2019 and 2020 seasons. One hundred pomegranate trees were chosen and sprayed three times at the beginning of flowering, full bloom, and 1 month later with the following treatments: water as control, 0.025, 0.05 and 0.1 mg/L Se; 5 mL/L, 7.5 and 10 mL/L Ag NPs, and 0.5, 1 and 2 mg/L K2Si2O5. The results showed that spraying of SE, Ag NPs, and K2Si2O5 ameliorated the shoot length, diameter, leaf chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Moreover, two flavonoids, namely rutin and apigenin, also appeared on the HPLC chromatogram of PPE with low concentrations. Our findings are in line with those obtained by Mosa et al [ 31 ], who reported that the main polyphenols in PPE include gallic acid, ellagic acid, quercetin, caffeic acid, p-coumaric acid, and vanillic acid. Fischer et al [ 32 ] investigated the polyphenols in pomegranate peels and they observed similar results but with different concentrations.…”
Section: Resultssupporting
confidence: 94%
“…Moreover, two flavonoids, namely rutin and apigenin, also appeared on the HPLC chromatogram of PPE with low concentrations. Our findings are in line with those obtained by Mosa et al [ 31 ], who reported that the main polyphenols in PPE include gallic acid, ellagic acid, quercetin, caffeic acid, p-coumaric acid, and vanillic acid. Fischer et al [ 32 ] investigated the polyphenols in pomegranate peels and they observed similar results but with different concentrations.…”
Section: Resultssupporting
confidence: 94%
“…Additionally, this treatment also improved the fruit weight, and length, along with increased the soluble solids as well as total, reduced, and non-reduced sugars in fruits. Simultaneously, it resulted in a reduction in juice acidity on opposite to not sprayed trees [81]. Additionally, the extern application of Se on blueberry at a complete flowering time and one month later, has been found to significantly enhance fruit quality, as well as the nutritional content of the trees [82].…”
Section: Discussionmentioning
confidence: 95%
“…Standard HPLC grade phenolic and flavonoid compounds (Fig. 3) including pyrogallol (1), quinol (2), gallic acid (3), catechol (4), p-hydroxybenzoic acid (5), chlorogenic acid (6), vanillic acid (7), caffeic acid (8), syringic acid (9), vanillin (10), p-coumaric acid (11), ferulic acid (12), benzoic acid (13), rutin (14), ellagic acid (15), o-coumaric acid ( 16), salicylic acid (17), resveratrol (18), cinnamic acid (19), myricetin (20), quercetin (21), rosmarinic acid (22), naringenin (23), and kaempferol (24) as well as caffeine (25), were used for the HPLC analysis. The detection was set at 284 nm to identify the existed compounds.…”
Section: Phytochemical Compositions Analysis By Hplcmentioning
confidence: 99%
“…Botanical extracts have been observed to inhibit the mycelial growth and spore germination of some plant pathogenic fungi [15,16]. Promising antifungal activity against Rhizoctonia solani was observed as wood samples from Melia azedarach treated with pomegranate peel extracts, where the HPLC analysis showed the presence of phenolic acid compounds, syringic, p-coumaric, benzoic, caffeic, gallic, ferulic, salicylic, cinnamic, and ellagic as well as catechol and pyrogallol [17]. Olive leaf extract showed potential antimicrobial activity and compounds oleuropein, caffeic acid, luteolin 7-O-glucoside, rutin, apigenin 7-O-glucoside verbascoside, and luteolin 4'-O-glucoside were identified by HPLC/DAD [18].…”
Section: Introductionmentioning
confidence: 99%